A Macrofinance Model for Option Prices: A Story of Rare Economic Events - Hasler, Michael; Jeanneret, Alexandre (Management Science, 2023)
We propose a macrofinance model that rationalizes robust features in equity index option markets. When rare disasters are followed by economic recoveries, the slope of the implied volatility term structure is positive in good times but turns negative in bad times. Additionally, implied volatility decreases with moneyness in bad times (volatility skew), whereas the shape becomes a smile in good times in the presence of rare economic booms. Our theory contributes to understanding the dynamics of the implied volatility surface yet keeping standard asset-pricing moments realistic. This paper was accepted by Gustavo Manso, finance. Funding: The authors are grateful to HEC Montreal, the University of Texas at Dallas, and particularly to the Canadian Derivatives Institute for generous financial support. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4587 .